2011
DOI: 10.1097/brs.0b013e3181e7f34b
|View full text |Cite
|
Sign up to set email alerts
|

Neural Stem Cells Modified by a Hypoxia-Inducible VEGF Gene Expression System Improve Cell Viability under Hypoxic Conditions and Spinal Cord Injury

Abstract: These results strongly suggest the potential utility of mNSCs modified by a hypoxia-inducible VEGF gene expression system in the development of effective stem cell transplantation protocols in SCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Consequently, additional administration of one of these factors can be applied as an alternative strategy to expensive hypoxic preconditioning. While erythropoietin already demonstrated a beneficial effect on the survival of different kinds of progenitor cells after transplantation [122-124], HIF-1α-transduced MSCs significantly improved myocardial infarction [125] and VEGF-overexpressing neural stem cells demonstrated higher cell survival in an injured spinal cord [126]. Attention needs to be paid to additional genetic or phenotypic alterations that might be introduced accidentally upon modification of MSCs in order to produce hypoxia-resistant cells.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, additional administration of one of these factors can be applied as an alternative strategy to expensive hypoxic preconditioning. While erythropoietin already demonstrated a beneficial effect on the survival of different kinds of progenitor cells after transplantation [122-124], HIF-1α-transduced MSCs significantly improved myocardial infarction [125] and VEGF-overexpressing neural stem cells demonstrated higher cell survival in an injured spinal cord [126]. Attention needs to be paid to additional genetic or phenotypic alterations that might be introduced accidentally upon modification of MSCs in order to produce hypoxia-resistant cells.…”
Section: Introductionmentioning
confidence: 99%
“…As early as in 2000, it was reported that VEGF and VEGF receptors in the spinal cord was induced after mechanical spinal injury and prostaglandin administration [17]. Later on, increases in VEGF-A have been shown to be beneficial for post-SCI recovery in most of the studies [18-21], although ineffective results have also been shown [22]. Nevertheless, adverse effects of VEGF-A have not been reported.…”
Section: Discussionmentioning
confidence: 96%
“…Because NSCs have the potential to differentiate into neurons (Lee et al, 2012), oligodendrocytes, and axons (Decimo et al, 2011;Yasuda et al, 2011) and also have the ability to fill the spinal cord cavity and blend with host spinal cord tissues (Boido et al, 2011;Li et al, 2011), they may be useful for repairing SCI. Animal experiments have indicated that the regenerated axon has limited ability to cross fiber scars to set up new neural pathways because the internal environment of the organism affects the survival and differentiation of NSCs (Lian Jin et al, 2011;Meng et al, 2011;Su et al, 2011;Wang et al, 2011;Wakai et al, 2014). Therefore, limited effects would be observed for the repair using only NSCs.…”
Section: Discussionmentioning
confidence: 99%